Caribbean Community agricultural policy (CARICOM Secretariat GeorgetownGY, 2011)
Outlines a long-term vision, goals, broad policy areas, specific policy objectives, immediate priorities and an implementation strategy for the Community agricultural policy. Aims to develop agriculture, fisheries and forestry in a regional framework and perspective.
Approved by the Thirty-Eighth Special Meeting of the Council for Trade and Economic Development (COTED), held in Dominica on 14 October 2011\n